IMPLEMENTATION OF SELF DIRECTED LEARNING TO INCREASE STUDENT LEARNING ACTIVENESS - Zubaidi, Ahmad; Amanah, Ilfatul (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Self-Directed Learning is an approach that emphasizes student independence in managing the learning process. However, the implementation of Self-Directed Learning faces challenges, especially for students who have limited time and energy to learn optimally. In coastal environments, many students are involved in helping their parents work as fishermen, which has an impact on their physical and mental condition during the learning process. This phenomenon causes some students to appear daydreaming in class, lose focus, and tend to be less active in participating in learning. This research aims to find out what form of strategy and implementation of Self-Directed Learning at MAN 1 Probolinggo is suitable for increasing their active participation in class. This research uses qualitative methods with interviews centered on students, teachers and parents in coastal environments as the main subjects. The research results show that the personal approach significantly increases student activity in class. Teachers who use this approach interact more often directly with students, both individually and in small groups. This interaction creates a comfortable and supportive learning atmosphere, so that students feel more confident to participate actively in learning.